The Pink Box: Exclusive Homochiral Aromatic Stacking in a Bis-perylene Diimide Macrocycle - Penty, Samuel E.; Zwijnenburg, Martijn A.; Orton, Georgia R.F.; Stachelek, Patrycja; Pal, Robert; Xie, Yujie; Griffin, Sarah L.; Barendt, Timothy A. (Journal of the American Chemical Society, 2022)
This work showcases chiral complementarity in aromatic stacking interactions as an effective tool to optimize the chiroptical and electrochemical properties of perylene diimides (PDIs). PDIs are a notable class of robust dye molecules and their rich photo- and electrochemistry and potential chirality make them ideal organic building blocks for chiral optoelectronic materials. By exploiting the new bay connectivity of twisted PDIs, a dynamic bis-PDI macrocycle (the “Pink Box”) is realized in which homochiral PDI–PDI π–π stacking interactions are switched on exclusively. Using a range of experimental and computational techniques, we uncover three important implications of the macrocycle’s chiral complementarity for PDI optoelectronics. First, the homochiral intramolecular π–π interactions anchor the twisted PDI units, yielding enantiomers with half-lives extended over 400-fold, from minutes to days (in solution) or years (in the solid state). Second, homochiral H-type aggregation affords the macrocycle red-shifted circularly polarized luminescence and one of the highest dissymmetry factors of any small organic molecule in solution (glum = 10–2 at 675 nm). Finally, excellent through-space PDI–PDI π-orbital overlap stabilizes PDI reduced states, akin to covalent functionalization with electron-withdrawing groups.
EPrint Processing Status: Full text deposited in DRO